Das fibröse Skelett der Hand: Veränderungen bei der Dupuytren-Kontraktur = The fibrous skeleton of the hand : changes with Dupuytren’s contracture - Langer, Martin Franz; Unglaub, Frank (Der Orthopäde, 2017)
The exact knowledge of the anatomy of the fibrous skeleton of the hand is an absolute prerequisite for any treatment of Dupuytren’s disease. The fibrous skeleton does not only include the palmar aponeurosis, but also numerous retinacula cutis, which are not found in current anatomy books. Here, eponyms facilitate the otherwise difficult and over-pronounced names of the fiber systems. Skoog, Legueu and Juvara, Gosset, Grapow, Grayson, Cleland, Thomine, and Barton are the most important. This systematic review of the fibers and strands is designed to help reduce iatrogenic complications.